Prevalence and Determinants of Self-reported Morbidity among Pregnant Women in Rural Areas of Pakistan - Midhet, Farid (Qassim University, Kingdom of Saudi Arabia, 2007)
BACKGROUND : The maternal mortality ratio (MMR) in Pakistan is estimated at 400 maternal deaths per 100,000 live births. Prevalence of minor and major illnesses related with pregnancy and childbirth is much higher. However, most births in the rural areas take place at home, conducted by untrained traditional birth attendants. Data on the prevalence of maternal morbidity is, therefore, limited. Self-reporting of illnesses related with pregnancy and childbirth is generally considered as unreliable, as women’s perception of the seriousness of the health problems is inadequate. METHOD : The data were collected in a baseline survey that was conducted for an operations research project of the Ministry of Health, Government of Pakistan. The baseline survey comprised interviews with the ever-married women in the reproductive ages (15–49 years). For the selection of eligible women for the interview, a two-staged cluster random sampling procedure was applied. The response rate was 94.4% and interviews with 9,118 of the identified 9,655 females were successfully completed. The interviews were conducted by female interviewers having graduate degree or above. Completed questionnaires were edited and coded by a team of professional data editors. RESULTS : The prevalence of maternal morbidity in this study was 20%, which is considered to be high, although can be expected in this population. Nearly half of the women reported some kind of illness during pregnancy, which is also expected. This study also estimated that the unmet obstetric need among rural women was very high; this finding has policy implication, as the need for alternative and more operational indicators of maternal health is increasingly felt. CONCLUSION : It is recommended that population-based studies and national surveys routinely incorporate well designed questions to elicit information on self-reported maternal morbidity; the same studies can also be used to identify the determinants of common obstetric problems and to estimate the unmet need of obstetric care.